STRATEGI PENCEGAHAN KEBAKARAN LAHAN BERBASIS MASYARAKAT DESA KUALA TERUSAN KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Evy Marta Meranty Folia; Zulfan Saam; Trisla Warningsih (Jurnal Ilmu Lingkungan, 2020)
The formulation of a strategy to prevent community-based land fires in Kuala Terusan Village was carried out in October 2018 to October 2019. The research method is survey method. Key informants included the Head of the Pelalawan District Disaster Management Agency, the Head of the Fire Regulations of the Pelalawan Regency Plantation Office, the Head of the Kuala Terusan Village, Community Leaders, the Chair of the Tuah Negeri farmer group and the Head of the Tanjung Mandiri farmer group. Key informants can increase if met by other parties who also play a role in preventing land fires in Kuala Terusan Village. Data analysis using SWOT analysis. The results of the formulation of the strategy are to increase community knowledge and attitudes towards preventing land fires through socialization, guidance and training, increasing community participation through institutional strengthening and providing incentives by the government to the Fire Concerned Farmers Group and Fire Concerned Communities, utilizing government resources and community capacity villages as a preventive measure for preventing land fires through building reservoirs, building canal blocks and providing infrastructure for preventing land fires for farmer groups, increasing collaboration between the government and the community through the establishment of a Patrol Team in efforts to prevent land fires and conducting routine patrol / supervision of migrants to the village which has the potential to cause a fire, maintain local wisdom of land clearing or preparation by not burning through the provision of assistance with tools and social assistance and issuing village regulations to improve ur rights, responsibilities and criminal provisions (legal sanctions) for communities in land management.